Cytokine-armed oncolytic herpes simplex viruses: a game-changer in cancer immunotherapy? - Howard L Kaufman; Hongbin Wang; Dipongkor Saha; Samuel D Rabkin; Mia Borlongan; Uyen Le; Hans J Nauwynck (Journal for ImmunoTherapy of Cancer)
Cytokines are small proteins that regulate the growth and functional activity of immune cells, and several have been approved for cancer therapy. Oncolytic viruses are agents that mediate antitumor activity by directly killing tumor cells and inducing immune responses. Talimogene laherparepvec is an oncolytic herpes simplex virus type 1 (oHSV), approved for the treatment of recurrent melanoma, and the virus encodes the human cytokine, granulocyte-macrophage colony-stimulating factor (GM-CSF). A significant advantage of oncolytic viruses is the ability to deliver therapeutic payloads to the tumor site that can help drive antitumor immunity. While cytokines are especially interesting as payloads, the optimal cytokine(s) used in oncolytic viruses remains controversial. In this review, we highlight preliminary data with several cytokines and chemokines, including GM-CSF, interleukin 12, FMS-like tyrosine kinase 3 ligand, tumor necrosis factor α, interleukin 2, interleukin 15, interleukin 18, chemokine (C-C motif) ligand 2, chemokine (C-C motif) ligand 5, chemokine (C-X-C motif) ligand 4, or their combinations, and show how these payloads can further enhance the antitumor immunity of oHSV. A better understanding of cytokine delivery by oHSV can help improve clinical benefit from oncolytic virus immunotherapy in patients with cancer.